International mediation as a distinct form of conflict management. Issue 1 (2014) - ,
Abstract : Purpose – This paper aims to provide a structured overview of the most important research conducted in the field of international mediation. Although there are still strong similarities between the processes of international and domestic mediation, lack of a clear structure on the international level suggests that international mediation activities could be separately academically scrutinized. This literature review is aimed at illustrating the unique nature of international mediation.Design/methodology/approach – Various factors that affect the overall process and the outcome of international mediation efforts were clustered in four distinct yet interrelated groups. The first section illustrates various mediators' characteristics that might induce the disputants to accept mediation and agree to specific terms that were mediated in the process. In the second section two distinct factors affecting the mediation outcome were explained: contextual and behavioral. Finally, in the third sections various types of mediators were discussed.Findings – The article shows the intricate complexities of international mediation, highlighting four distinct features that might have an effect on the mediation outcome: mediator's characteristics, contextual features, behavioral factors, and types of mediators.Originality/value – This article attempts to offer a comprehensive overview of the current state of the art in international mediation, and suggests potential areas of future research.